Variations in epidermal cytochrome oxidase activity after local irradiation - Itoiz, María Elina; Molinari de Rey, Beatriz L.; Cabrini, Rómulo Luis (Chapman and Hall Ltd., 1982)
Fil: Itoiz, María Elina Comisión Nacional de Energía Atómica; Argentina